2022
DOI: 10.1101/2022.12.01.518747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Young Plasma Rejuvenates Blood Dna Methylation Profile, Prolongs Mean Lifespan and Improves Health in Old Rats

Abstract: There is converging evidence that young blood conveys cells, vesicles and molecules able to revitalize function and restore organ integrity in old individuals. Here, we assessed the effects of young rat plasma on the lifespan, epigenetic age and healthspan of old female rats. Beginning at 25.3 months of age, a group of 9 rats (group T) was i.p injected with plasma from young rats (2 months) until their natural death. A group of control rats of the same age, received no treatment. Blood samples were collected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
3
0
0
Order By: Relevance
“…Detailed values can be found in Supplementary Table S13 Our study presents compelling evidence for epigenetic age reversal in rats via the administration of exosome-containing fraction derived from plasma of young adult pigs. Following our initial report in 2020 [48], additional validation and cross-species evidence affirmed our results [43,[49][50][51]. Mice studies confirmed that young plasma, administered through heterochronic parabiosis, rejuvenated solid organs, reduced epigenetic age by up to 30%, and extended both lifespan and healthspan, with the effect persisting post-separation [50].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Detailed values can be found in Supplementary Table S13 Our study presents compelling evidence for epigenetic age reversal in rats via the administration of exosome-containing fraction derived from plasma of young adult pigs. Following our initial report in 2020 [48], additional validation and cross-species evidence affirmed our results [43,[49][50][51]. Mice studies confirmed that young plasma, administered through heterochronic parabiosis, rejuvenated solid organs, reduced epigenetic age by up to 30%, and extended both lifespan and healthspan, with the effect persisting post-separation [50].…”
Section: Discussionsupporting
confidence: 84%
“…Our results are consistent with the results from a different evaluation of young whole plasma extracted from young rats. In this study, whole plasma from young rats (2 months) was intraperitoneally injected into 25-month-old rats until their natural death [43]. As in the current study, this separate investigation using whole plasma also found that very soon following treatment, the DNAm age of the treated rats fell below that of controls and remained lower until the end of their lives [43].…”
Section: Second E5 Methylation Experiments In Bloodsupporting
confidence: 63%
“…Our study presents compelling evidence for epigenetic age reversal in rats via the administration of exosome-containing fraction derived from plasma of young adult pigs. Following our initial report in 2020 [48], additional validation and cross-species evidence affirmed our results [43,[49][50][51]. Mice studies confirmed that young plasma, administered through heterochronic parabiosis, rejuvenated solid organs, reduced epigenetic age by up to 30%, and extended both lifespan and healthspan, with the effect persisting post-separation [50].…”
Section: Discussionsupporting
confidence: 84%